Literature Review; Stabilitas Tanda-tanda Vital Neonatus Segera Mandi dengan Tunda Mandi - Ompusunggu, Fransiska; Rustina, Yeni (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2021)
Introduction: Bathing of neonate is aÂ part of the birth process by cleaning the baby's body, watering or soaking. However, neonates may experience heat loss more rapidly and show signs of vital instability. Objectives: The purpose of this study was to compare the stability of the vital signs of neonates who immediately took a bath and who delayed bathing. Methods: the research method as a comprehensive search strategy, namely articles in the database of research journals through the Scopus database, Proquest, Clinical Key, and Science Direct with full text criteria and published in years. 2016-2020. Results: The results obtained in this study indicate that it is advisable to delayed bathing in newborns so that the stability of vital signs is better